2018
DOI: 10.2147/dddt.s164324
|View full text |Cite|
|
Sign up to set email alerts
|

Theaflavin alleviates inflammatory response and brain injury induced by cerebral hemorrhage via inhibiting the nuclear transcription factor kappa β-related pathway in rats

Abstract: ObjectiveIntracerebral hemorrhage (ICH) is one of the most common acute cerebrovascular diseases with high mortality. Numerous studies have shown that inflammatory response played an important role in ICH-induced brain injury. Theaflavin (TF) extracted from black tea has various biological functions including anti-inflammatory activity. In this study, we investigated whether TF could inhibit ICH-induced inflammatory response in rats and explored its mechanism.Materials and methodsICH rat models were induced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…From the dataset, after comparing the gene expression data obtained from ICH tissue with that obtained from the contralateral brain tissues, we obtained 67 DEGs. GO analysis indicated that the main functional annotation results were consistent with those obtained by previous reports, i.e., a significant increase in inflammatory response promotes ICH-induced brain injury, which may be one of the main factors contributing to the poor prognosis in patients with ICH (Boehme et al, 2018; Fu et al, 2018). The immune response can antagonize the inflammatory response, induced after an episode of cerebral hemorrhage, to reduce the secondary damage to brain tissue, and thereby improve the recovery of nerve function (Klebe et al, 2015; Lu et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…From the dataset, after comparing the gene expression data obtained from ICH tissue with that obtained from the contralateral brain tissues, we obtained 67 DEGs. GO analysis indicated that the main functional annotation results were consistent with those obtained by previous reports, i.e., a significant increase in inflammatory response promotes ICH-induced brain injury, which may be one of the main factors contributing to the poor prognosis in patients with ICH (Boehme et al, 2018; Fu et al, 2018). The immune response can antagonize the inflammatory response, induced after an episode of cerebral hemorrhage, to reduce the secondary damage to brain tissue, and thereby improve the recovery of nerve function (Klebe et al, 2015; Lu et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…From the GSE24265 dataset, after comparing the gene expression data obtained from ICH tissue with that obtained from the contralateral brain tissues, we obtained 67 DEGs. GO analysis indicated that the main functional annotation results were consistent with those obtained by previous reports, i.e., a significant increase in inflammatory response promotes ICH-induced brain injury, which may be one of the main factors contributing to the poor prognosis in patients with ICH (Boehme et al 2018;Fu et al 2018). The immune response can antagonize the inflammatory response, induced after an episode of cerebral hemorrhage, to reduce the secondary damage to brain tissue, and thereby improve the recovery of nerve function (Klebe et al 2015;Lu et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Theaflavin (TF) is a distinctive derivative of benzotropolones first extracted from black tea, and has been shown to have antioxidant effects for its functions of radical scavenging and metal chelation 6 , 7 . A number of studies have revealed the treatment efficacy of TF in various diseases, such as cardiovascular disease 8 , inflammatory disorders 9 , fatty liver 10 , and bacterial and viral infection 11 . These beneficial effects have been attributed to the regulation of endogenic antioxidant systems and scavenging of excessive ROS 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%